Clinicoepidemiological Profile of Elderly PLHIV Attending a Tertiary Care Center in South India. (November 2017) - Madi, Deepak; Ramakrishnan, Neha; Unnikrishnan, Bhaskaran; Ramapuram, John; Achappa, Basavaprabhu; Rathi, Priya
Background: Physicians are coming across a considerable number of HIV-positive patients belonging to older age-group, in practice. They pose a challenge as they might present with advanced forms and comorbid conditions. We aimed to describe the clinicoepidemiological profile of elderly people living with HIV. Methodology: We conducted a cross-sectional study at Kasturba Medical College, Mangalore. We analyzed the record of 120 patients from 2009 to 2014. Descriptive statistics were used to describe sociodemographic and clinical profile of patients. Results: Of 786 HIV-positive patients, 120 were elderly. Mean age was 55.9 ± 6.1 years. Majority 68% were male. In all, 63.33% were male. Commonest route of transmission was heterosexual intercourse, most presented at World Health Organization (WHO) stage 1 (64.17%). In all, 77.5% had hypertension and 26.6% had tuberculosis. The median CD4 count at presentation was 245 cells/mm 3 (145-426 cells/mm 3 ). Forty-two percent were late presenters (CD4 <200 cells/mm 3 ). Conclusion: Treating physician should have a high index of suspicion in diagnosing HIV among elderly age-group.